Integration of CVD graphene in gaseous electron multipliers for high energy physics experiments - Orlandini, G.; Brunbauer, F.; Coletti, C.; Convertino, D.; Doser, M.; Floethner, K.; Janssens, D.; Lisowska, M.; Mishra, N.; Oliveri, E.; Ropelewski, L.; Scharenberg, L.; et al. (Journal of Instrumentation, 2023)
To enhance the performance of micro-patterned gaseous detectors (MPGDs) to meet the challenging requirements of future high energy physics (HEP) experiments, two-dimensional (2D) materials are attractive candidates to address the back flow of positive ions, which affects detector performance by distorting electric field lines. In this context, graphene is promising to work as selective filter for ion back flow suppression, being transparent to electrons while at the same time blocking ions. Also, graphene membranes can physically separate drift and amplification regions of the detectors, offering additional flexibility in the choice of gas mixtures and allowing independent optimizations of detector sensitivity and electron multiplication processes. Here we present an approach to integrate graphene grown via chemical vapor deposition (CVD) on gaseous electron multiplier (GEM) prototypes via a wet transfer procedure in order to suspend graphene over thousands of holes with 60 μm diameter and overcome the challenges encountered due to process steps involving liquids, mostly related with the capillary effects during drying and evaporation of them. In order to overcome the risk of damaging the membrane and decreasing the yield of suspended 2D material membranes, critical point dryer (CPD) and inverted floating method (IFM) procedures are investigated. In addition to the necessity to cover the full holes in the active area, polymeric residuals have to be minimized in order to evaluate the graphene transparency at the electron energies (i.e., < 15 eV) typically obtained in the operating conditions, measurements in these energy ranges are still not deeply investigated.
CRIS-Team Scopus Importer:2023-10-13
Keywords: Gaseous detectors; Materials for gaseous detectors; Micropattern gaseous detectors (MSGC; GEM; THGEM; RETHGEM; MHSP; MICROPIC; MICROMEGAS; InGrid; etc)